PENGARUH PENGETAHUAN PAJAK, TARIF PAJAK DAN SANKSI PAJAK TERHADAP KEPATUHAN WAJIB PAJAK KENDARAAN BERMOTOR: KEPATUHAN WAJIB PAJAK KENDARAAN BERMOTOR - Meyla Novita (Yayasan Kayyis Mulia Jaya, 2024)
This research aims to find out whether there is a significant relationship between tax knowledge, tax rates and tax sanctions. The research method used is general-probability sampling using a judgmental or purposive sampling technique, in other words, the process of drawing a sample which is carried out based on criteria that have been determined by the researcher. The benefits of this research for academics are as further reference material in matters relating to taxpayer compliance, increasing knowledge and insight regarding tax matters, and being able to benefit from research experience. The practical benefit is as a contribution to efforts to increase taxpayer compliance, namely by knowing the factors that can influence taxpayer compliance, which in this research is taxpayer knowledge, tax rates and tax sanctions, especially for the research location area. The results of this research show that tax knowledge, tax rates and tax sanctions simultaneously (simultaneously) affect taxpayer compliance. Taxpayer years have a positive influence on the compliance of vehicle taxpayers, Tax rates do not have a positive influence on compliance with vehicle taxpayers, Tax sanctions have a positive influence on compliance with vehicle taxpayers. Keywords: Tax knowledge, tax rates, tax sanctions, taxpayer compliance